Trends in Urological Referral Patterns: A Study of Community and University Urologists in the United States. Issue 6 (November 2018) - Terlecki, Ryan P.; Miller, Nicole L.; Inman, Brant A.
Abstract : Introduction: : Numerous factors are associated with changes in practice patterns, some provider specific (eg age, gender, training, practice type, sense of well‐being) and others extrinsic (eg changes in reimbursement, medicolegal environment, government involvement). Through the American Urological Association Leadership Program we evaluated trends in same specialty referral patterns among U.S. urologists. Methods: : We queried case logs from the American Board of Urology and analyzed case trends from 2005 to 2015. Additionally, we surveyed practicing urologists regarding perceived trends in referral patterns during the last 5 years and their opinion regarding principal drivers of change. Results: : The number of female urologists is increasing, as is subspecialization. Open surgical cases are decreasing in number as laparoscopic, robotic and percutaneous procedures are increasing. Female urology procedures have decreased dramatically. Survey results suggest that compared to 5 years ago, urologists are increasingly likely to refer cases to another provider for all queried operations other than transurethral benign prostatic hyperplasia procedures. Cases within oncology and reconstruction/prosthetics were associated with the highest reported avoidance. The most common factors influencing the decision to refer were surgical training (48.1%), change in practice type (36.7%), complications (25.5%), medicolegal concerns (22.2%) and reimbursement (21%). Conclusions: : Trends in urological referral patterns show an increased likelihood of referral for common urological surgical procedures, regardless of subspecialty or disease. While most referrals are reportedly directed to academic medical centers, there appears to be an increasing trend toward internal referral among practices. The most commonly cited factor for referral was surgical training, which has implications for physician education.